Magnetic reconnection and modification of the Hall physics due to cold ions at the magnetopause. Issue 13 (5th July 2016) - André, M.; Li, W.; Toledo‐Redondo, S.; Khotyaintsev, Yu. V.; Vaivads, A.; Graham, D. B.; Norgren, C.; Burch, J.; Lindqvist, P.‐A.; Marklund, G.; Ergun, R.; Torbert, R.; et al.
Abstract: Observations by the four Magnetospheric Multiscale spacecraft are used to investigate the Hall physics of a magnetopause magnetic reconnection separatrix layer. Inside this layer of currents and strong normal electric fields, cold (eV) ions of ionospheric origin can remain frozen‐in together with the electrons. The cold ions reduce the Hall current. Using a generalized Ohm's law, the electric field is balanced by the sum of the terms corresponding to the Hall current, thev  × B drifting cold ions, and the divergence of the electron pressure tensor. A mixture of hot and cold ions is common at the subsolar magnetopause. A mixture of length scales caused by a mixture of ion temperatures has significant effects on the Hall physics of magnetic reconnection. Key Points: Verification at high resolution that cold ions introduce a new length scale at the magnetopause Verification at high resolution that cold ions modify the Hall physics of magnetic reconnection and reduce Hall currents Separatrix normal electric field balanced by the Hall term, the cold ion term, and the divergence of the electron pressure tensor